Analyses of the Distribution Patterns of Burkholderia pseudomallei and Associated Phages in Soil Samples in Thailand Suggest That Phage Presence Reduces the Frequency of Bacterial Isolation - Withatanung, Patoo (PLoS Negl Trop Dis, 2016)
BACKGROUND: Burkholderia pseudomallei is a soil saprophytic bacterium that causes melioidosis. The infection occurs through cutaneous inoculation, inhalation or ingestion. Bacteriophages (phages) in the same ecosystem may significantly impact the biology of this bacterium in the environment, and in their culturability in the laboratory. METHODS/PRINCIPAL FINDINGS: The soil samples were analysed for the presence of bacteria using culture methods, and for phages using plaque assays on B. pseudomallei strain 1106a lawns. Of the 86 soil samples collected from northeastern Thailand, B. pseudomallei was cultured from 23 (26.7%) samples; no phage capable of infecting B. pseudomallei was detected in these samples. In contrast, phages capable of infecting B. pseudomallei, but no bacteria, were present in 10 (11.6%) samples. B. pseudomallei and their phages were co-isolated from only 3 (3.5%) of soil samples. Since phage capable of infecting B. pseudomallei could not have appeared in the samples without the prior presence of bacteria, or exposure to bacteria nearby, our data suggest that all phage-positive/bacteria-negative samples have had B. pseudomallei in or in a close proximity to them. Taken together, these findings indicate that the presence of phages may influence the success of B. pseudomallei isolation. Transmission electron microscopy revealed that the isolated phages are podoviruses. The temperate phages residing in soil-isolated strains of B. pseudomallei that were resistant to the dominant soil borne phages could be induced by mitomycin C. These induced-temperate phages were closely related, but not identical, to the more dominant soil-isolated phage type. CONCLUSION/SIGNIFICANCE: The presence of podoviruses capable of infecting B. pseudomallei may affect the success of the pathogen isolation from the soil. The currently used culture-based methods of B. pseudomallei isolation appear to under-estimate the bacterial abundance. The detection of phage capable of infecting B. pseudomallei from environmental samples could be a useful preliminary test to indicate the likely presence of B. pseudomallei in environmental samples.